Analisis Determinan Kebijakan Dividen Perusahaan Consumer Non-Cyclicals yang Terdaftar di Indeks Saham Syariah Indonesia - Faisal Ihsannuddin; Kristianingsih Kristianingsih; Hazma Hazma (Journal of Applied Islamic Economics and Finance, 2022)
The purpose of this study was to determine the factors that influence dividend policy. This study examines the effect of leverage as measured by the Debt to Equity Ratio, free cash flow, and collateralizable assets on dividend policy as measured by the Dividend Payout Ratio. The type of research used is quantitative research, and the population used in this study is non-cyclical consumer companies that are members of the ISSI for the 2016-2020 period. Obtained as many as 16 companies that meet the criteria to be used as research samples. The data analysis technique used is multiple linear regression analysis on panel data. The results showed that partially, Leverage and Free Cash Flow had a negative and insignificant effect on Dividend Policy, while Collateralizable Assets had no significant positive effect on Dividend Policy. In addition, dividend policy is affected by Leverage, Free Cash Flow and Collateralizable Assets simultaneously.